GERAKAN SOSIAL BARU PERSPEKTIF KRITIS: RELAWAN POLITIK DALAM PILPRES 2014 DI SURABAYA - Purboningsih, Sayekti Dwi (Jurnal Review Politik, 2015)
The article aims to answer the questions about the commencement process of volunteer group as a new social movement and to analyze it in a critical perspective. The research employed a descriptive-quali-tative method based on case study. The results of the research show that the establishment of political volunteer groups has been mainly triggered by people’s dissatisfaction over the policies promul¬ga¬ted by the previous Indonesian government. These people have organized themselves to support Joko Widodo as the presidential candidates. The second reason, based the critical perspective, is closely related to individual and collective actions to act voluntarily based on rational awareness. These people see Joko Widodo as a humble and honest person who possesses high integrity and personality of leadership and also has experiences in managing two big cities, i.e. Solo and Jakarta